2018
DOI: 10.1080/21645515.2018.1498282
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a spleen registry on optimal post-splenectomy vaccination and care

Abstract: Although registrants are receiving initial and booster vaccinations, they do not receive newly recommended vaccines. In order to maintain long-term adherence, we recommend streamlining health information systems, improving awareness strategies and improving financial access to vaccinations in the community with additional awareness of the activities of the registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Unlike the United Kingdom, the Spleen Australia, a clinical service based at The Alfred Hospital in Melbourne, provides education and ongoing management recommendations for patients and their physicians. Studies have shown that our local clinical registry, the Spleen Australia clinical registry, has a positive effect on patient uptake of ongoing (booster) vaccinations,8486 is associated with a reduction in invasive pneumococcal disease,87 and is cost-effective in its activities 88. Improved uptake of vaccination with participation with a registry program has also been shown elsewhere 80.…”
Section: Solutionsmentioning
confidence: 85%
“…Unlike the United Kingdom, the Spleen Australia, a clinical service based at The Alfred Hospital in Melbourne, provides education and ongoing management recommendations for patients and their physicians. Studies have shown that our local clinical registry, the Spleen Australia clinical registry, has a positive effect on patient uptake of ongoing (booster) vaccinations,8486 is associated with a reduction in invasive pneumococcal disease,87 and is cost-effective in its activities 88. Improved uptake of vaccination with participation with a registry program has also been shown elsewhere 80.…”
Section: Solutionsmentioning
confidence: 85%
“…Recent work in other regions of France and Australia also showed a low pneumococcal vaccination rate of 18.8 and 7%, respectively [ 10 , 15 ]. Similar to our study, international studies have reported a pneumococcal vaccination rate between 60 and 88% [ 10 , 12 , 16 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A dedicated healthcare network has been reported useful for the follow-up of asplenic patients in several countries [ 21 , 28 32 ]. Moreover, creating nationwide registries of asplenic patients has correlated with improved implementation of established guidelines among physicians and allowed for the dissemination of useful information, medical advice, and vaccination reminder in a cost-effective manner [ 15 , 26 , 33 ]. We insist on the central role of hospital specialists taking care of the patient before and at the time of splenectomy for starting the preventive measures against infection, and beginning patient’s medical education about his future asplenic state.…”
Section: Discussionmentioning
confidence: 99%
“…45 Assessment of adherence to guidelines and long-term management demonstrated that 77% had good knowledge of key educational points to reduce the chances of infection, but they were less likely to receive the most recent vaccines. 46 The majority were taking or had used antibiotic prophylaxis (70%) and had a supply of emergency antibiotics (66%). More than 12 000 patients are registered (June 2023), including 89% postsplenectomy, 6% with a non-functioning spleen and 5% previously treated by splenic artery embolisation.…”
Section: Registriesmentioning
confidence: 99%